Flood risk management strategies for national capital territory of Delhi, India. Issue 3 (2nd September 2019) - Kumar, Mukesh; Sharif, Mohammed; Ahmed, Sirajuddin
Abstract: Delhi, a mega city with a population of 16.78 million, is situated on the bank of River Yamuna. During the last three decades, the hydrological characteristics of the Yamuna River basin have significantly changed. Due to rapid urbanization in the basin, the runoff has considerably increased. Consequently, the flooding events are now occurring more frequently and with higher magnitudes. A sizeable population of the city of Delhi resides in settlements that have mushroomed in the flood plains of Yamuna. A majority of these settlements is in the low-lying areas, which make them highly vulnerable to flooding events of even moderate intensity. In the present paper, several structural and non-structural measures for the management of flood risk in the national capital territory of Delhi have been recommended. A critical analysis of the existing flood control measures has revealed several shortcomings. Based upon the analysis, several implementable structural and non-structural measures for alleviating the problem of riverine as well as urban flooding in the national capital territory of Delhi have been recommended. Proper implementation of the recommended structural and non-structural measures could significantly reduce the flood risk associated with riverine and urban flooding in the national capital territory of Delhi.